Investigation into the correlation between humanistic care ability and emotional intelligence of hospital staff - Jingjing Ma; Wentao Peng; Jihong Pan (BMC, 2022)
Abstract Background There are different degrees of flaws in the knowledge structure of humanistic medicine of medical staff. The level of emotional intelligence of medical staff affects their career development as well as their relationship with patients. Currently, the research on humanistic care ability (HCA) and emotional intelligence of medical staff in China and other countries is rare. This study aimed to investigate the correlation between the level of HCA and level of emotional intelligence of the whole hospital staff. Methods The questionnaire survey employed contained self-designed questions on the hospital staff members' socio-demographic background, Caring Ability Inventory, and Wong and Law Emotional Intelligence Scale. The survey was conducted with the staff of West China Second University Hospital, Sichuan University in April 2020. Results The hospital staff's average CAI score was 197.77 ± 20.30, and their average WLEIS score was 84.21 ± 13.48. The CAI and WLEIS scores of the hospital staff who chose their college majors on their own interests were higher than those who chose their majors for other reasons (employability, suggestions from family or others, etc.). The CAI and WLEIS scores of the hospital staff who had received more comprehensive and in-depth humanistic care training were higher than those who did not. The CAI score of the hospital staff who had participated in volunteer service activities was higher than those who did not. The WLEIS score of the Pediatrics Department staff was higher than that of the Outpatient and Emergency Department staff, and the difference was statistically significant (P < 0.05). The scores of emotional intelligence, self-emotion assessment and expression, self-emotion management, self-emotion utilization, emotion recognition of others, and HCA of the hospital staff were positively correlated (P < 0.001). Conclusion There were different levels of development of internal factors of emotional intelligence among the hospital staff, and their humanistic care ability was at a low level. Emotional intelligence was positively correlated to humanistic care ability. The findings suggest in-service training and education by healthcare institutions to enhance healthcare staff's emotional intelligence for promoting the general health of the population.